Comparative Analysis of Dimensional Accuracy of Two Types of Silicone Impression Materials: Optosil and Elite-HD - Amini Parviz; Amin Rahpeyma; Maryam Hejazi (Journal of Dental Materials and Techniques, 2017)
Statement of the Problem: Understanding about impression materials, their properties, uses and manipulation can guide operators towards having more successful restorations. Purpose: The aim of this in vitro study was to compare the accuracy of a condensation silicone impression material, Optosil, and an addition poly siloxane impression material, Elite-HD. Materials and Method: A laboratory model with two metallic dies was used to make impression. A horizontal notch on one of the two dies simulated an undercut. Ten impressions were made by each impression material by the putty-wash technique. After pouring impressions with velmix die stone, a total of 20 stone casts were made from both materials. Measurements of casts were compared with the master model. Statistical analyses were performed using t-test. Result: This results of this study showed that the height of die without undercut decreased in both groups. Also the height above the undercut decreased in both groups, which was more obvious in Elite-HD group than Optosil group. The distance between dies increased in both groups, with higher figures for Elite-HD. So, Optosil is a more accurate material for registering inter-abutment distance than Elite-HD. The diameter of die under the undercut decreased in Optosil group and was similar to the master model in Elite-HD. Statistical analysis showed significant differences between these two groups in the distance between abutments (p=0.001), the diameter of die under the undercut (p=0.014) and the height of  die above undercut(p=0.057). Conclusion: Optosil is more accurate in registering inter-abutment distance than Elite-HD, so Optosil is preferred for fixed partial denture impressions. Since Elite-HD showed more accuracy in C measurements than Optosil, it is preferred for single crown impressions.